O bairro Guapiruvu como lugar-organização: uma abordagem institucional do organizar - Grigoletto, Fábio (2018)
In recent years, a large process of establishing cooperatives in rural agrarian reform settlements has been observed in Brazil. Different researchers have interpreted this emergency as a result of incentives to cooperativism enrolled in public food procurement schemes like Food Procurement Program (PAA) and School Feeding National Program (PNAE). Although research on the subject diverges on the validity of this organizational form as a tool for organizing settlements, little attention has been given to the different practices used by the members of these cooperatives to keep them operating. The objective of this research is to understand how the maintenance of organizations of family farmers in spaces impacted by land reform takes place. To do so, it adopts a procedural vision of the organization, emphasizing its emergence through social interactions situated in time and space. This view, based on the approach of organizing, seeks to integrate some assumptions of organizational institutionalism. The study was conducted at a neighborhood called Guapiruvu, located at Sete Barras, a municipality of Ribeira Valley. The place was adopted as the level of analysis. Understanding that action and the construction of meanings do not take place in a vacuum, but rather as a continuous and historically situated process that is delimited by local and extra-local meaning systems, this research concludes that maintenance takes place through practices of institutional mediation based on the delimitation of the boundaries of organizing and, in addition, the institutionalization of contradictions as a form of accommodation of inconsistencies and tensions between institutional arrangements that overlap in place without, however, being convergent. In order to do so, it proposes an analytical model appropriate to an institutional approach of the organizing that allows performing diachronic analyzes. By doing this, it allowed to identify the relevant role of history in the formation of beliefs and emotions that permitted the re-signification of institutions such as family and religion, thus composing its substance.